Infectious hematopoietic necrosis virus virological and genetic surveillance 2000–2012. Issue 1 (January 2017) - Breyta, Rachel; Brito, Ilana; Kurath, Gael; LaDeau, Shannon
Abstract: Surveillance records of the acute RNA pathogen of Pacific salmonid fish infectious hematopoietic necrosis virus are combined for the first time to enable landscape‐level ecological analyses and modeling. The study area is the freshwater ecosystems of the large Columbia River watershed in the U.S. states of Washington, Oregon, and Idaho, as well as coastal rivers in Washington and Oregon. The study period is 2000–2012, and records were contributed by all five resource management agencies that operate conservation hatcheries in the study area. Additional records from wild fish were collected from the National Wild Fish Health Survey, operated by the U.S. Fish and Wildlife Survey. After curation and normalization, the data set consists of 6766 records, representing 1146 sample sites and 15 different fish hosts. The virus was found in an average of 12.4% of records, and of these 66.2% also have viral genetic analysis available. This data set is used to conduct univariate ecological and epidemiological analyses and develop a novel hierarchical landscape transmission model for an aquatic pathogen.